Perceived social pressures and the internalization of the mesomorphic ideal: The role of drive for muscularity and autonomy in physically active men. (March 2016) - Edwards, Christian; Tod, David; Molnar, Gyozo; Markland, David
Highlights: Perceived pressure predicted mesomorphic ideal internalization in males. Pressure predicted internalization indirectly via drive for muscularity. Autonomy moderated both the direct and indirect relationships. Abstract: We examined if there were both direct and indirect relationships (via the drive for muscularity) between the perceived pressure to be muscular and internalization of the mesomorphic ideal, and if autonomy moderates these relationships in physically active men. A sample of 330 men, who were undergraduate students studying sport, completed the Behavioral Regulation in Exercise Questionnaire-2, the Mesomorphic Ideal Internalization subscale of the revised male version Sociocultural Attitudes Toward Appearance Questionnaire, the Perceived Sociocultural Pressure Scale-Modified, and the Drive for Muscularity Scale Attitudes subscale. Perceived pressure predicted internalization directly, and indirectly through the drive for muscularity. The direct relationship between pressure and internalization was weaker under higher levels of autonomy. The indirect path, via drive for muscularity, was stronger under higher levels of autonomy. These results provide insights into why men vary in the degree to which they internalize pressure to develop a mesomorphic ideal, supporting further examination of autonomy.